In silico design of novel dihydropteridone derivatives with oxadiazoles as potent inhibitors of MCF-7 breast cancer cells - Aloui, Mourad; El fadili, Mohamed; Er-rajy, Mohammed; Mujwar, Somdutt; Abuelizz, Hatem A.; Er-rahmani, Sara; Menana, Elhalaoui (Frontiers in Chemistry, 2025)
IntroductionPharmaceutical treatment protocols or combination therapies based on chemical compounds make it possible to target cancer cells, which can be complicated by several factors, including their resistance to bioactive compounds and the potential for drugs to damage certain healthy cells.MethodsThis project was designed to assess the structural relationship between new dihydropteridone-derived compounds bearing an oxadiazole moiety and their corresponding cytotoxicity against breast cancer, using computational chemistry tools. The aim of this research is to better understand how compound properties influence their activity and to understand the underlying mechanisms, which could then be integrated into the anticancer drug design process with a view to recommending new optimized compounds likely to have the desired activity.Results and discussionsThe results show that the predicted molecules possess enhanced selective cytotoxic inhibitory activity against breast cancer cells (MCF-7). Guided by these analyses, we designed five novel dihydropteridone derivatives incorporating an oxadiazole moiety. These compounds exhibited favorable interactions with key breast cancer-related proteins, demonstrated enhanced dynamic stability within their binding sites, and adhered to established drug-likeness principles. Importantly, these compounds displayed promising oral absorption (88%) in preliminary assessments and exhibited no significant toxicity. These findings suggest that these novel dihydropteridone-oxadiazole derivatives warrant further investigation as potential multifunctional agents for the treatment of breast cancer cells (MCF-7).